Integrate moral, religious values in education system - Hasan, Md. Mahmudul (New Straits Times Press (M) Berhad, 2018)
I am not suggesting that education should be otherworldly and out of touch with contemporary society and its structures. What I argue for here is the integration of moral and religious values in pedagogical practices. The best way to address the educational crisis is the integration approach to embrace the faith and learning. This involves inculcating religious and universally accepted moral values in teaching and learning.